Estimating Lcal Poverty Measures Using Satellite Images : A Pilot Application to Central America - Klemens, Ben; Coppola, Andrea; Shron, Max (World Bank, Washington, DC, 2015)
Several studies have used satellite measures of human activity to complement measures of economic production. This paper builds on those studies by considering satellite measures for improving poverty measures. The paper uses local-scale census and survey data from Guatemala to test at how fine a scale satellite measures are useful. Results show that supplementing survey data with satellite data leads to improvements in the estimates.